Space vector-based three-level discontinuous pulse-width modulation algorithm - Beig, Abdul Rahiman; Kanukollu, Saikrishna; Dekka, Apparao (IET power electronics, 2013)
Discontinuous pulse-width modulation (PWM) techniques result in reduced power loss in voltage source inverters. This study presents the space vector approach to the three-level discontinuous PWM technique. The switching sequences for four basic types of discontinuous PWM and the implementation are presented. An improved discontinuous PWM algorithm is presented for low modulation index region. All these algorithms are verified experimentally and the results are presented. The performance of discontinuous PWM algorithms is compared with that of conventional space vector-based PWM algorithms.